THE EFFECT OF DISCIPLINE AND MOTIVATION ON EMPLOYEE PERFORMANCE IN THE GIORDANO LADIES DIVISION AT PT. GIORDANO INDONESIA - Riri Oktarini; Ana Septia Rahman; Dewi Nari Ratih Permada (International Journal Multidisciplinary Science, 2024)
The objective of this research is to determine the influence of discipline and motivation on employee performance in the Giordano Ladies division at PT. Giordano Indonesia. This study employs a quantitative approach with associative methods. Data collection techniques were carried out through questionnaires. The research population includes all employees of the Giordano Ladies division at PT. Giordano Indonesia, totaling 60 individuals. Data analysis techniques use multiple linear regression analysis with the assistance of SPSS 25.00 software. The results of this study indicate that there is a positive and significant influence of discipline and motivation on the performance of employees in the Giordano Ladies division at PT. Giordano Indonesia. The research also found that there is a positive and significant influence of motivation on the performance of employees in the Giordano Ladies division at PT. Giordano Indonesia. The results show that there is a positive and significant joint influence of discipline and motivation on the performance of employees in the Giordano Ladies division at PT. Giordano Indonesia.